Experimental Abdominal Sepsis: Sticking to an Awkward but Still Useful Translational Model - Federica Murando; Andrea Peloso; Lorenzo Cobianchi (Hindawi Limited, 2019)
Animal models are widely used to replicate human intra-abdominal infections. Different methodologies have been described and proposed in the scientific literature, including injection and surgical models. The aim of this review is to recapitulate the advantages and disadvantages of each method to help choose the most appropriate model for individual experimental purposes.